A Systematic Review on Unique Characteristics of Generation Z and Their Impact on Purchasing Decisions - Espejo, Luis; Perez, Nelly; Mendoza, Cecilia; Gagarín, Yuri (Journal of Ecohumanism, 2024)
The Generation Z, also recognized as "centennials," stands out for its complete immersion in technology, exerting a significant influence on their purchasing decisions. This study applied the PRISMA method to conduct a systematic review of the distinctive attributes of this generation and their impact on consumer choices. Results, extracted from 14 articles analyzed between 2019 and 2023, indicate an increase in scientific production in 2023, with a notable focus on purchasing trends. Indonesia emerges as a focal point of research, demonstrating a particular interest in the consumption practices of Generation Z. "Sustainability" leads in publications, emphasizing the convergence between youth and sustainable consumption. Scopus stands out as the primary database, indicating a preference for journal articles. Generation Z, identified by its connection to digital commerce and the influence of social media, especially TikTok, exhibits a blend of contemporary and traditional values in their purchasing decisions. Their focus on adopting innovative technologies and the meticulous evaluation of sustainability and cost reflect thoughtful and critical consumption. In conclusion, Generation Z redefines the market landscape with an innovative and socially conscious perspective, underscoring the importance of authentic and personalized strategies in an ever-evolving commercial environment.